Good Teachers: Indonesia’s Perspective - Titik Ulfatun (JPP (Jurnal Pendidikan dan Pembelajaran), 2021)
Teachers play an important role in enhancing the standard of education. It might mean that having high-quality or good teachers might lead to high-quality education. However, there is no single clear definition of what good teachers are. This literature review paper will try to explore a brief view of what good teachers are and how to make good teachers generally and specifically from Indonesia’s perspective. The term of good teachers covers both subjective and objective things from personalities to qualifications, abilities, and competencies. The ways to make good teachers could start from teacher recruitment, education, status, distribution, support, until teacher reward